The Great Powers in Latin America - Comparison of the United States and the Chinese Foreign Policies - Henriquez Argote, Jose Luis; Maslowski, Nicolas, 1972-; Durrmeyer, Sébastien; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2013)
Latin America is in the last years a region who is receiving more and more global attention both on the economic and political side. During the last 30 years the region has gone through several changes allowing the Latin American countries to maintain a fast and stable economic and democratic growth which has attracted the interest of the two main economic powers, the United States and the People's Republic of China. Since the Monroe Doctrine, the United States has significantly contributed to shaping policy in Latin America. However, given the recent changes in the international system since the end of the Cold War, the U.S. influence has decreased probably as never before. This has allowed other international powers, precisely China, to enter the region and gain important economic and political partners. Given China's need for commodities, energy and the need for new markets for their high amounts of manufactures, Latin America has gone off very well in increasing its economical ties with China. However, it must not be forgotten that the United States still plays an important role in the region. The aim of this thesis is to compare the current foreign policies of the United States and the China towards Latin America, of where is the arm of the United States important, and where the Chinese one is.
Vedoucí práce: Nicolas Maslowski
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses